PENENTU CAPITAL ADEQUACY RATIO PADA BANK UMUM YANG TELAH GO PUBLIC DI BURSA EFEK INDONESIA (BEI) - Fifi Nur Aisyah, 14.05.52.0047; Taswan, Taswan (Students' Journal of Accounting and Banking, 2018)
This study aims to analyze the effect of Return On Equity, Net Interest Margin, Loan to Deposit Ratio and Non Performing Loan of Capital Adequacy Ratio Banking companies listed on the Indonesia Stock Excange. In this study, researchers used purposive sampling and sample size 110 companies obtain convensional bank in Indonesia, Bank Indonesia registered in the year 2012 to 2016. Hypothesis tesing using t - test with a significance level of 5%. The result showed that Return On Equity have negative significant, Net Interest Margin have positive and significant, Loan to Deposit Ratio have negative and not significant, and Non Performing Loan have negative and not significant to Capital Adequacy Ratio.Key Words : ROE, NIM, LDR, NPL and CAR